Efektivitas penerapan bimbingan konseling islami mengatasi mental korban bullying pada siswa sekolah menengah pertama - Elvin, Said Devi; Sufri, Sofyan; Isneini, Isneini; Mawarpury, Marty; Fithria, Fithria (Holistik Jurnal Kesehatan, 2024)
Background: Bullying in the school environment causes students to feel depressed and not want to go to school, which leads to depression, anxiety, stress and suicidal behavior. Purpose: To analyze the effectiveness of the application of Islamic counseling guidance in overcoming the mental condition of bullying victims in junior high school students. Method: Quasi-experiment with a control group was used in three junior high schools in Banda Aceh City. Bullying conditions among students at the research location were selected through screening and determining the sample size based on power analysis with a medium effect size, power (0.08), 95% confidence level and alpha 0.05. The total sample was 192 students divided into three groups, namely the Islam-based intervention group (n=64), the health-based intervention group (n=64) and the control group (n=64). The three groups were evaluated at baseline (pre-test), one week after the intervention (post test 1) and 1 week after post-test 1 (post-test 2) using The Olweus Bully Victim Questionnaire and Depression Anxiety and Stress Scales - Youth version (DASS-Y). The intervention was carried out using face-to-face guidelines. Results: Shows that the Islam-based group experienced a decrease in bullying behavior (p=0.000), stress (p=0.014), anxiety (p =0.014) and depression (p =0.014) after the intervention. Between the Islam-based group, health-based group and control group there were significant differences after one week of intervention (post-test 1) in the conditions of bullying (p =0.000), stress (p =0.002), anxiety (p = 0.030) and depression (p = 0.006). The same thing also happened after one week post-test 1 (post-test 2), where there were significant differences in the conditions of bullying (p =0.000), stress (P=0.000), anxiety (p =0.006) and depression (p = 0.001). Conclusion: The bullying prevention program has a significant influence on the incidence of bullying or psychological disorders. Islamic-based bullying prevention has been proven to be effective in reducing bullying incidents and improving psychological status.   Keywords: Guidance and Counseling; Bullying; Islam; Students; Victim Mentality.   Pendahuluan: Bullying di lingkungan sekolah menimbulkan perasaan depresi pada siswa dan tidak ingin bersekolah sehingga berujung pada depresi, kecemasan, stres dan perilaku bunuh diri. Tujuan: Untuk menganalisis efektivitas penerapan bimbingan konseling islami mengatasi mental korban bullying pada siswa sekolah menengah pertama. Metode: Quasi eksperimen dengan kelompok kontrol digunakan di tiga SMP di Kota Banda Aceh. Kondisi bullying di kalangan pelajar di lokasi penelitian dipilih melalui screening dan penentuan jumlah sampel berdasarkan analisis kekuatan dengan effect size sedang, power (0.08), tingkat kepercayaan 95% dan alpha 0.05. Jumlah sampel sebanyak 192 siswa yang terbagi dalam tiga kelompok yaitu kelompok intervensi berbasis Islam (n=64), kelompok intervensi berbasis kesehatan (n=64) dan kelompok kontrol (n=64). Ketiga kelompok tersebut dievaluasi pada awal (pre-test), satu minggu setelah intervensi (post test 1) dan 1 minggu setelah post-test 1 (post-test 2) menggunakan The Olweus Bully Victim Questionnaire dan Depression Anxiety and Stress Scales - Youth version (DASS- Y). Intervensi dilakukan dengan menggunakan pedoman yang dilakukan secara tatap muka. Hasil: Menunjukkan bahwa kelompok berbasis Islam mengalami penurunan perilaku bullying (p=0.000), stres (p=0.014), kecemasan (p=0.014), dan depresi (p=0.014) setelah dilakukan intervensi. Antara kelompok berbasis Islam, kelompok berbasis kesehatan, dan kelompok kontrol terdapat perbedaan yang signifikan setelah satu minggu intervensi (post-test 1) pada kondisi bullying (p=0.000), stres (p=0.002), kecemasan (p= 0.030) dan depresi (p= 0.006). Hal serupa juga terjadi setelah satu minggu post-test 1 (post-test 2), terdapat perbedaan yang signifikan pada kondisi bullying (p=0.000), stress (p=0.000), kecemasan (p=0.006), dan depresi (p= 0.001). Simpulan: Program konseling bullying memiliki pengaruh yang signifikan terhadap kejadian bullying ataupun gangguan psikologis. Konseling bullying berbasis Islami terbukti efektif mengurangi kejadian bullying dan meningkatkan status psikologis.   Kata Kunci: Bimbingan Konseling; Bullying; Islami; Mental Korban; Siswa.